IOP Conference Series: Earth and Environmental Science - Sarychev; Chinakhov Specialist in the field of welding production Associate Professor of Yurga technological Institute of Tomsk Polytechnic University; Solodsky specialist in the field of ecology and life safety Associate Professor of Yurga technological Institute of Tomsk Polytechnic University, candidate of technical sciences; Granovskii; Nevskii (2017)
World production of surfacing materials requires a large amount of alloying elements extracted from the Earth crust. Efficient use of scarce alloying elements and development of resource efficient surfacing techniques which reduce consumption of alloying elements together with improvement of the functional properties of the surfaced layer is a relevant problem of material science and preservation of the environment. In the paper the authors consider the problem of modeling the convective flows emerging under the plasma jets in the process of surfacing. The authors formulate the basic requirements to the thermal cycle of the surfacing ensuring obtaining identical functional properties of the surface while the amount of scarce alloying elements reduces.